BOOK REVIEW: KARL OVE KNAUSGÅRD, “LUPTA MEA CARTEA A TREIA: INSULA COPILARIEI”, TRADUCERE DIN LIMBA NORVEGIANĂ DE ROXANA-EMA DREVE, EDITURA LITERA, BUCUREȘTI, 2016, 510 P. - POPA, Ștefana Teodora (Studia Universitatis Babeș-Bolyai Philologia, 2017)
My struggle: Book 3. Boyhood Island is the third volume of the six-part novel My struggle (Min Kamp in original Norwegian), remarkably translated into Romanian directly from Norwegian by Roxana-Ema Dreve. The project My Struggle has generated intense and opposite reactions among Scandinavian scholars while its author, Karl Ove Knausgård, was considered both the best and the worst writer of our times. Now an international best-seller, the whole series is strongly autobiographical, summing up the life of its author, until the age of 45. In the first two volumes, A death in the family (Min Kamp 1) and A man in love (Min Kamp 2), Knausgård juggles with the recollection of his past and the reality of the present while he is constantly exploring his inner thoughts and feelings and exposes them to the public, with no visible shame. Regardless of the dark tone that accompanies the first book or the more positive one in the second, the one thing that remains unchanged is the dominant, painful and God-like presence of a father. After reading the first book, it becomes clear enough that the narrator’s father was a very much hated person by his sons, without telling exactly why. The problematic relationship between them is explored even deeper in A man in love, but the father remains a mysterious character.